Best Machine Learning Model For Face Recognition in Home Security Application - Istiqomah; Faqih Alam; Achmad Rizal (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2023)
Particularly since the COVID-19 outbreak, Indonesia has seen an annual surge in criminal prosecutions. To increase home security, many technological advances have been made. Face recognition served as the main form of security for almost all of them. Face detection, face segmentation, and face recognition are the three steps in the face recognition process. To avoid misclassification and increase system dependability, accurate recognition of faces becomes crucial in security systems. The optimization tool Grid Search CV produces using a number of machine learning methods that are proposed. Each machine learning has been created using its best model and has attained accuracy levels of at least 90%. The most effective strategy is SVM, which has 100% accuracy rates. A technique for choosing the best model is an alternative. The computation time will be compared to that of more complex systems before these results are eventually communicated to the real system